Systems Engineering Practices Exhibited in the Creation of a Film Original Score. Issue 1 (28th October 2015) - Salado, Alejandro; Salado, Carlos
Abstract: Systems engineering has been successfully applied to a wide variety of industries, which include defense, space, energy, or transportation. All those systems have in common that they are engineered systems and/or socio‐technical ones. Yet, systems engineering is considered both an art and a science. Therefore, could systems engineering be or have been applied in the domain of art, even if not done explicitly? Being one of the authors of this paper a systems engineer and the other one a music composer, this paper reports on the reflections of mutual discussions about how each of us of carried out our activities in our respective domain. Interestingly, it turns out that engineering a space system and creating a film original score abstractly follow the same set of principles and practices.